1999
DOI: 10.1007/bf02347394
|View full text |Cite
|
Sign up to set email alerts
|

Archaeometrical studies of Greek and Roman silver coins

Abstract: Quantitative analyses of various silver coins from the first century BC, found on current Romanian territory (Thasian tetradrachmae, Apollonia and Dyrrachium drachmae, Roman republican denarii) were performed using PIXE (3 MeV external proton beam) and XRF (1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Measurements have shown that the quality of silver drachms degraded from an initial ~98% Ag value down to 70-90% until the middle of the first century BC [5]. This degradation may explain the significant differences in Cu and Ag concentration between the Hungarian and Romanian coins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements have shown that the quality of silver drachms degraded from an initial ~98% Ag value down to 70-90% until the middle of the first century BC [5]. This degradation may explain the significant differences in Cu and Ag concentration between the Hungarian and Romanian coins.…”
Section: Resultsmentioning
confidence: 99%
“…Four years ago, the Romanian co-authors of the present paper also started a comprehensive and systematic study of the coin-hoards discovered in Romania the results of which will be published elsewhere [5]. The existence of similar artefacts at the Hungarian National Museum (HNM) led to this collaboration in order to reveal connections between drachms found in the neighbouring countries.…”
Section: Introductionmentioning
confidence: 91%
“…A conventional electronic chain, consisting of preamplifier and MCA, is used to accumulate the spectra [Bugoi R., 1999].…”
Section: Methodsmentioning
confidence: 99%
“…and Bugoi et al . classified ancient coins from the fourth to first century bc by their places of origin and recovery also by using PCA . Minemasa et al .…”
Section: Introductionmentioning
confidence: 99%